Politics of religious freedom in the Asia-Pacific: an introduction - Hurd, Elizabeth Shakman (Journal of religious and political practice, 2018)
This article introduces the main arguments of Beyond Religious Freedom and situates them in the context of this special issue on the politics of religious freedom in the Asia Pacific. It discusses the intensification of state-sponsored global religious interventionism that led me to write the book, and explains how the questions raised by the new global politics of religion came to seem urgent and important. It then presents the book's central organizing framework of the '3 religions' (expert, lived, and governed) as a set of heuristics for examining these co-productions of religion, law and politics. A final section weaves together insights from other contributors to this special issue with the claims of Chapter 4 of the book to explore the politics of religious freedom in the Asia-Pacific.